TAMAR JAYA'S ACTIVISM IN STRENGTHENING AND PRESERVING ENREKANG MUSIC CULTURE IN SOUTH SULAWESI - Ilham, Ilham; Aji Manggala, Bondan; Darlenis, Teti (Institut Seni Indonesia (ISI) Surakarta, 2025)
This article explores the contributions of Tamar Jaya as an art activist committed to advocating for the preservation of traditional music in Enrekang, a region characterized by its remoteness and lack of external support. This study applies a qualitative methodology, utilizing a character study framework based on Abdul Mustakim. It incorporates a historical lens and individual life narratives to explore his life journey, intellectual contributions, original concepts, and the socio-historical backdrop that influenced his activism. The findings indicate that Tamar Jaya's decisions are shaped by an intellectual wisdom acquired after higher education, which fosters a critical viewpoint on the stagnation within the arts ecosystem in South Sulawesi. This perspective particularly highlights the deficiencies in life skills among artists and the fluctuating political commitment from the local government. His activism unfolded in two strategic phases: an initial decade-long grassroots initiative (Gerakan Akar Rumput) aimed at revitalizing communal traditions, followed by a shift towards embodying a cultural survivor through the adoption of a hybrid Artist-Farmer model, characterized by a nuanced approach to political engagement. This study can be used to describe the Tamar Jaya activism movement as a model of cultural-political management, which aims to maintain and disseminate the existence of marginalized arts and culture by optimizing management skills, networks, and funding literacy.